Desenvolvimento de um rastreador estrelar (Star Tracker) de baixo custo e código aberto - Lessa, Caio (Universidade Federal de São Carlos, 2025)
With technological advancements and the consequent reduction in costs, access to cameras and equipment for night sky observation has become easier, contributing to the popularization of astrophotography, a practice that consists of photographing astronomical objects through long-exposure imaging. Under these conditions, the apparent motion of celestial bodies, especially stars, becomes more evident in the images, forming trails known as star trails, caused by Earth’s rotation relative to the equipment. To compensate for this effect and allow for longer exposures, star trackers are used. However, their high cost limits access for beginners and enthusiasts. This work proposes the development of a low-cost, open-source star tracker, offering an accessible alternative for long-exposure astrophotography. The device operates through the motorization of an equatorial mount, with most of its parts produced using FFF 3D printing and low-cost components. Tests were conducted with the equipment to determine the maximum exposure time achievable through proper alignment with Earth’s rotational axis. The results indicate that it is possible to reach exposures of up to five minutes, a value more than 180 times greater than that obtained without motion compensation, in addition to reducing by nearly 93% the total storage volume required for the images, due to the smaller number of photos needed to achieve the same total exposure time, thus validating the effectiveness of the proposed solution.
Development of a low-cost, open-source star tracker
Keywords: Montagem Equatorial; Star-tracker; Astrofotografia; Longa Exposição; Impressão 3D; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS; 9. Indústria, Inovação e Infraestrutura